Construction verification and modeling of acoustic measuring probe - Sheremeta, Roman; Ferens, Oleksandr (Видавництво Львівської політехніки, 2022)
The paper presents a study of wave processes occurring in the experimental measuring acoustic probe. The probe is designed for contactless measurement of linear dimensions and micro-movements of physical objects using acoustic oscillations in the sound range. In the course of the study, an equivalent circuit of the probe in the form of a T-link band electric K-filter was drawn up. According to the design geometric parameters of the acoustic probe, the electrical parameters of the K-filter components are calculated. To verify the theoretical results, a set of experimental equipment was developed, and a method of experimental research was developed. Experimental studies have confirmed the possibility of designing acoustic probe using the proposed method of calculating the geometric parameters of its elements.
Keywords: measurement; contactless method; acoustics; interference; standing wave; microdisplacement; simulation; experiment